2002
DOI: 10.1103/physrevb.65.144303
|View full text |Cite
|
Sign up to set email alerts
|

Lattice vibrations ofαNaV2O5

Abstract: We report high resolution polarized infrared studies of the quarter-filled spin ladder compound α ′ -NaV2O5 as a function of temperature (5 K≤ T ≤ 300 K). Numerous new modes were detected below the temperature Tc = 34 K of the phase transition into a charge ordered nonmagnetic state accompanied by a lattice dimerization. We analyse the Brillouin zone (BZ) folding due to lattice dimerization at Tc and show that some peculiarities of the low-temperature vibrational spectrum come from quadruplets folded from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
12
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
(145 reference statements)
5
12
0
2
Order By: Relevance
“…6 and found by other groups 32,41 . The two low frequency modes, at 68 and 106 cm −1 , are the strongest.…”
Section: C-axis Phononssupporting
confidence: 51%
See 1 more Smart Citation
“…6 and found by other groups 32,41 . The two low frequency modes, at 68 and 106 cm −1 , are the strongest.…”
Section: C-axis Phononssupporting
confidence: 51%
“…Modes at frequencies close to 68 and 106 cm −1 have been found by Raman spectroscopy 42,43 . Sample dependence of mode frequencies by few wavenumbers has been observed both in infrared 32 and Raman 43 . It is known that Na deficiency of α ′ -Na x V 2 O 5 affects T c and in samples where x = 0.97 the phase transition is suppressed completely 44 .…”
Section: C-axis Phononsmentioning
confidence: 98%
“…10-12͒ and far-infrared spectroscopy. 13,14 Meanwhile, a peak, which grows enough below T c and coincides approximately with the E g + spin-gap energy, was observed at about 64 cm −1 by Raman-scattering measurements. [15][16][17][18][19] Moreover, Konstantinović et al 20 found another peak at 86 cm −1 , which probably corresponds to the E g − magnetic excitation, by means of Raman scattering using the 647.1 nm light of Kr + -ion laser.…”
Section: Introductionmentioning
confidence: 75%
“…11 In the lowtemperature phase, ions are displaced from their original positions by distances of the order of 0.05 Å. These displacements have been observed in x-ray diffraction [12][13][14][15][16][17] and can be estimated from infrared 18 and Raman spectroscopy. 19 They stabilize a phase containing zig-zag charge-ordering patterns.…”
Section: Introductionmentioning
confidence: 95%